Pathophysiological Role of Synovitis in Hemophilic Arthropathy Development: A Two-Hit Hypothesis - Calcaterra, Ilenia; Iannuzzo, Gabriella; Dell’Aquila, Francesco; Di Minno, Matteo Nicola Dario (Frontiers in Physiology, 2020)
Despite an increasing access to prophylaxis with clotting factor concentrates, arthropathy still represents the main chronic complication of hemophilia. Whereas previous studies described hemophilic arthropathy (HA) as a degenerative arthropathy, somehow resembling osteoarthritis (OA), most recent evidence suggests that complex inflammatory and immunologic mechanisms are also involved in the pathophysiology of HA. In the present review, we described available data on major mechanisms leading to arthropathic changes in patients with hemophilia, with a specific focus on the role of synovium. The presence of hemosiderin in the joint space induces synovium proliferation, thus leading to formation of several lytic enzymes determining chondrocytes apoptosis and proteoglycans levels reduction. This leads to a direct joint “chemical” damage representing early damages in the pathogenesis of HA (first hit). In parallel, synovial membrane and synovial endothelial cells become a dynamic reservoir of inflammatory cells and mediators, and propagate the inflammatory response (second hit), switching the process from a chemical damage to an inflammatory damage. Overall, consistent data pointed out synovitis as the keystone in HA pathophysiology. This opens novel potential therapeutic targets in this clinical setting.